PENGEMBANGAN INSTRUMEN PENILAIAN KETERAMPILAN BERNALAR KRITIS PADA MATERI PEMBANGUNAN BERKELANJUTAN DAN KELANGKAAN BAGI SISWA SMP - Sihombing, Azmho; Wasino; Supriyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a critical reasoning skills assessment instrument on sustainable development and scarcity materials for junior high school students. The method used was development research with the ADDIE model. The research subjects were seventh grade students of SMP Negeri 2 Lumbanjulu and SMP Negeri 2 Satu Atap Sibisa. The content validity of the instrument was analyzed using Aiken's V obtained a value of V>0.79 indicating validity in the aspects of content suitability, construction and language. Construct validity obtained an eigenvalue of 41.7% which was categorized as good. Empirical validity showed that 28 items met the criteria with an outfit mean square value < 1.2 and 2 items did not meet the criteria with an outfit mean square value > 1.2. Rasch modeling analysis shows the item reliability value of 0.86 and is categorized as good and the person reliability value is 0.81 including in the good category. The level of difficulty of the question is divided into 4 namely very difficult (7.14%), difficult (39.29%), easy (46.43%), and very easy (7.14%). Analysis of the practicality of the instrument obtained an average value of 91.25% which was categorized as very practical.